Thymoquinone loaded in nanostructured lipid carrier showed enhanced anticancer activity in 4T1 tumor-bearing mice. (20th July 2018) - Ong, Yong Sze; Saiful Yazan, Latifah; Ng, Wei Keat; Abdullah, Rasedee; Mustapha, Noordin M; Sapuan, Sarah; Foo, Jhi Biau; Tor, Yin Sim; How, Chee Wun; Abd Rahman, Napsiah; Zakarial Ansar, Fatin Hannani
Aim: To investigate the enhancement of anticancer activity of thymoquinone (TQ) by the use of nanostructured lipid carrier (NLC) in 4T1 tumor-bearing female BALB/c mice.Material & methods: TQ was incorporated into NLC (TQNLC) by using high pressure homogenization. TQNLC and TQ were orally administered to the mice.Results & conclusion: TQNLC and TQ are potential chemotherapeutic drugs as they exhibited anticancer activity. The use of NLC as a carrier has enhanced the therapeutic property of TQ by increasing the survival rate of mice. The antimetastasis effect of TQNLC and TQ to the lungs was evidence by downregulation of MMP-2. TQNLC and TQ induced apoptosis via modulation of Bcl-2 and caspase-8 in the intrinsic apoptotic pathway.